ANALYZING WORK VALUES OF GENERATION Z: IMPLICATIONS ON JOB RETENTION - Khaliunaa Dashdondog (Journal of Business and Innovation (Бизнес & Инноваци), 2024)
The scarcity of a youthful workforce in Mongolia has become a pressing issue, highlighting the need for a detailed understanding of the work values of Generation Z (Gen Z). Despite the importance of this demographic, there is a notable lack of research focused specifically on the work values of Gen Z within the Mongolian context. Addressing this gap, this study uses a qualitative approach to explore the factors that influence Gen Z’s job tenure and their reasons for leaving employment. By engaging with Gen Z employees across various sectors, this research provides an in-depth examination of their work values, uncovering key motivations that drive their employment decisions. Our findings reveal that Gen Z’s place more importance on intrinsic and altruistic values, such as personal growth and societal contribution etc., rather than extrinsic factors like salary or reputation. Furthermore, a preference for collaborative and flexible work environments was also evident, suggesting that traditional hierarchical organizational structures are less appealing to this cohort. This study contributes to the broader discourse on generational shifts in work values and their impact on organizational management, specifically within the rapidly evolving socio-economic landscape of Mongolia.